British engagement with Japan, 1854-1922 : the origins and course of an unlikely alliance - Best, Antony, 1964- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book by a leading authority on Anglo-Japanese relations reconsiders the circumstances which led to the unlikely alliance of 1902 to 1922 between Britain, the leading world power of the day and Japan, an Asian, non-European nation which had only recently emerged from self-imposed isolation. Based on extensive original research the book goes beyond existing accounts which concentrate on high politics, strategy and simple assertions about the two countries' similarities as island empires. It brings into the picture cultural factors, particularly the ways in which Japan was portrayed in Britain, and ambivalent British attitudes to race and supposed European superiority which were overcome but remained difficulties. It charts how the relationship developed as events unfolded, including Japan's wars against China and Russia, and in addition looks at royal diplomacy, where the Japanese Court came eventually to be treated as a respected equal. Overall, the book provides a major reassessment of this important subject.
Introduction 1. The Opening, 1854-69 2. The Age of Treaty Revision, 1870-1894 3. The Road to the Alliance, 1894-1902 4. Britain and the Russo-Japanese War, 1902-06 5. Managing the Alliance, 1906-14 6. The End of the Alliance, 1914-22 Conclusion
OCLC-licensed vendor bibliographic record.
Keywords: Great Britain -- Foreign relations -- Japan; Japan -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- 1837-1901.; Great Britain -- Foreign relations -- 1901-1936.; Japan -- Foreign relations -- 1868-1912.; Japan -- Foreign relations -- 1912-1926.; SOCIAL SCIENCE / Ethnic Studies / General